La reforma de los procedimientos especiales del Consejo de Derechos Humanos: ¿una mejora de los mecanismos extra convencionales? - Gifra Durall, Julia (Anuario de Derechos Humanos. Nueva Época, 2009)
The United Nations Human Rights Council, created in 2006, was established with the attempt to remedy some of the negative aspects and problems of its predecessor, the Human Rights Commission. Having this objective, it incorporates new elements not only in its position within the United Nations structure but also in its membership and control mechanisms, also known as “extra conventional mechanisms”. In this context, it stands out the special procedures reform, specially, since the adoption of a Code of Conduct for the “special rapporteurs” and experts of the Human Rights Council. This reform process has to be evaluated under the criteria of improving the effectiveness and impartiality of the special procedures.
Keywords: Human Rights Council; Special procedures; Experts; Ra¬pporteurs; United Nations; Code of conduct